Comparative Media Policy, Regulation and Governance in Europe Unpacking the Policy Cycle (Intellect, 2018)
Comparative Media Policy, Regulation and Governance in Europe - Unpacking the Policy Cycle represents the continuation and further development of a long tradition of media policy books, focusing on the development of media structures and media policy within Europe. It provides a comprehensive overview of the current European media in a period of more or less disruptive transformation. It maps the full scope of contemporary media policy and industry activities while also assessing the impact of new technologies and radical changes in distribution and consumption on media practices, organisations and strategies. Dealing with a good selection of critical issues in comparative media policy, regulation and governance, the book combines a critical assessment of media systems with a thematic approach. It starts out with the state of affairs at the level of media platforms, approaching these from a functional perspective, i.e. opinion and debate, news provision and entertainment. The book is both an academic book and a text book, as well as a source providing good practices for steering media policy, international communication and the media landscape across Europe.
English
Keywords: Business ethics & social responsibility; Media studies; Media, information & communication industries; TV & society; consumption; european media; international communication; media governance; media policy; media regulation; new technology